Local newforms for generic representations of unramified even unitary groups I: Even conductor case - Hiraku Atobe (Forum of Mathematics, Sigma)
In this paper, we define compact open subgroups of quasi-split even unitary groups for each even non-negative integer and establish the theory of local newforms for irreducible tempered generic representations with a certain condition on the central characters. To do this, we use the local Gan–Gross–Prasad conjecture, the local Rankin–Selberg integrals and the local theta correspondence.